MOLECULAR EPIDEMIOLOGY OF MULTIDRUG RESISTANT ENTEROBACTER CLOACAE BLOOD ISOLATES FROM A UNIVERSITY HOSPITAL - Dobromira Dimitrova; Temenuga Stoeva; Rumyana Markovska; Petya Stankova; Kalina Mihova; Radka Kaneva; Ivan Mitov (Peytchinski Publishing, 2019)
urpose: to evaluate the epidemiological relationship between 3rd generation cephalosporin resistant Enterobacter cloacae blood isolates collected from patients in the University Hospital in Varna city during the period March 2014 and January 2017 and to characterize the ESBLs production in these isolates. Materials and methods: a total of 47 consecutive (nonduplicate) 3rd generation cephalosporin resistant isolates of Enterobacter cloacae, obtained from blood samples of patients admitted in different wards in Varna University Hospital, were investigated. Antimicrobial susceptibility to set of antimicrobial agents was tested by disc diffusion method and Phoenix (BD), and the results were interpreted according to EUCAST guidelines 2017. Identification of ESBL encoding genes was performed by PCR and sequencing. Isolates were genotyped by ERIC PCR. Results: The antimicrobial susceptibility in the whole collection of isolates, shown in decreasing order, is as follows: amikacin, 97.8% < levofloxacin, 76.6% < trimethoprime/ sulphometoxazole, 40.4% < ciprofloxacin, 19% < gentamicin, 8.4% < cefepime, 4.2% < piperacillin/ tazobactam, tobramycin, 2.1%. Multidrug resistance was detected in 70.2% of the isolates. The most widespread enzyme was CTX-M-15, found in 95.5% (n=43). Nine different ERIC types were detected. The dendrogram of similarity revealed three main clones of E. cloacae: Clone I, comprising two closely related subclones (ERIC type A and Aa) (similarity coefficient 0.92), was predominant, detected in Haematology (n=9), Haemodialysis (n=8), ICU (n=6), Cardio surgery (n=3), Pulmonology (n=4) and Gastroenterology (n=1); Clones II (ERIC type C) and III were presented by 5, and 3 isolates with identical profiles, obtained from patients, hospitalized in different wards. The ERIC profiles K, L, M and P, were found in single isolates only and were interpreted as sporadic. Conclusions: multi-drug resistance in E. cloacae was associated with successful intrahospital dissemination of three CTX-M-15 producing E. cloacae clones. Clone I was predominant, demonstrating high cross-transmission, epidemic and invasive potential. BlaCTX-M-15 was identified as a major mechanism of resistance to 3rd generation cephalosporins in E. cloacae.